Perubahan Budaya Komunikasi pada Pengguna Whatsapp di Era Media Baru - Rifqi Fauzi (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2018)
Abstract A total of 63 million Indonesians are currently active as internet users and 95% of Indonesians use the internet to access social networks. This new media era makes social media a prima donna primarily to establish social relationships in cyberspace. With smartphones that support the WhatsApp app as one of the contemporary social media that is widely used by digital natives. As a creative generation in using technology, digital natives make use of WhatsApp as a communication medium today. WhatsApp users can continuously form a habit that eventually becomes a culture of communication. In this study, researchers interested to examine the digital communication culture natives formed by the use of social media WhatsApp. The purpose of this research is 1) To know the culture of digital communication natives on the use of WhatsApp. 2) To know the communication culture formed from the use of WhatsApp by digital natives. This type of research uses qualitative research with constructivist paradigm using virtual ethnography research approach. The data collection techniques are done by interviewing online and offline and make observations made through chat history and activities use WhatsApp features by informants. The results showed that there is a change in communication culture in the conventional era into the new medi era, ie from face to face communication to computer mediated communication. For digital natives, the established communication culture is a textile culture by building the value of emotional closeness and ease in conveying information, and embracing the norm of speed, entertainment, customization and freedom. Keywords: Communication Culture, New Media Era, WhatsApp, Digital Natives.